PERAN CONCIERGE DALAM MENINGKATKAN KUALITAS PELAYANAN FRONT OFFICE DEPARTMENT PADA RENAISSANCE HOTEL & RESORT OKINAWA - Raihanafa, Indira; Wijoyo, Tuwuh Adhistyo (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to Identify the obstacles Concierge faces in serving guests Study the efforts of Concierges in providing optimum service Formulate solutions to improve the quality of the service of the concierge Qualitative research methods are used by conducting semi-structured interviews with the staff of the Concierge at the Renaissance Hotel & Resort Okinawa. Research results show that: Concierge faces several obstacles, such as staff constraints, lack of knowledge, and ineffective communication. Concierge makes various efforts to provide optimal service, such as improving skills and knowledge, communicating well, and leveraging technology. Solutions to improve the quality of Concierge services include enhanced resources, training, and coordination. This study concludes that: Concierge plays an important role in improving the quality of service in the Front Office. Increased quality of Concierge service will enhance the hotel's reputation and provide guests with an unforgettable experience